Petrology of a supra-subduction zone ophiolite (Elazig, Turkey) - Beyarslan, M; Bingöl, AF (Canadian Science Publishing, Nrc Research Press, 2000)
The Elazig region in eastern Taurus, Turkey, exposes Paleozoic-Tertiary metamorphic, magmatic, and sedimentary units. Contacts between the different units are mostly tectonic, but there are also primary sedimentary, and intrusive contacts. The metamorphic rocks of the Elazig region are the Bitlis-Puturge and Keban-Malatya massifs, which are a single tectonostratigraphic unit that has been tectonically disrupted and fragmented during the Upper Cretaceous. Magmatic rocks in the region are represented by ophiolitic units, magmatic arc products, and young volcanic rocks. The sedimentary units are represented by Upper Cretaceous - Tertiary marine and lacustrine sedimentary rocks. In the study area, the metamorphic units are represented by the Paleozoic Puturge metamorphic rocks composed of phyllite, slate, mica schist, quartz-muscovite schist, calc-schist, and low-grade metamorphite. The ophiolite that is described in this paper is composed of wehrlite-pyroxenite, gabbro, diabase dykes, and dykes cutting gabbro. These units are cut by the granitic rocks of the Upper Cretaceous Elazig magmatic suite. The lithological and geochemical data on the rocks of Komurhan ophiolite indicate that these rocks were derived from crystallization of an enriched mid-ocean ridge basalt (MORB)-type magma. The Komurhan ophiolite formed in a supra-subduction spreading zone during the Cretaceous; related to this event is the north-dipping subduction of the southern branch of Neo-Tethys ocean, which began spreading in the Late Triassic. The crust was thickened by the development of an island arc and by the thrusting of the Puturge metamorphic rocks onto this island arc in response to north-south compression during the Late Cretaceous. The magma formed by partial melting of the subducted slab giving rise to granitic rocks that cut the upper parts of the ophiolite. The ophiolite and the Elazig magmatic suite attained their present position after the Middle Eocene.
Keywords: Orogenic Belt; Evolution; Rocks; Classification; Geochemistry; Petrogenesis; Model